Kerja Sama Guru PAI dan Orang Tua dalam Menjaga Iffah Ssiswi SMP - Yulfina; Mardianto (Cetta: Jurnal Ilmu Pendidikan, 2023)
One of the problems that has existed for a long time but has now become a very clear normalization is dating relationship. When woman no longer understand how valuable they are and lust become the controller between woman and man, the more corrupt the people of the end of this age will become. The religious sharia is increasignly foreign because there is no effort to explore and understand the wisdom behind the sharia command itself. Because woman are so glorified in Islam, they must understand very well the importance of maintaining purity and self honor. This research aims to explain the importence of cooperation between PAI teachers and parents in implementing iffah attitudes in guardianship children and importence of syncronizhing the cultivation of iffah attitudes at home and school. This type of qualitative research with descriptive methods and direct observation is complemented by various references sourched from theses, journals, and other collections of scientific works. The results showed that IT Junior High Schools was very possible to implement a boarding school system such as a separate learning building between male and female students to limit relationship and keep unwanted things from happening. As Islam teaches muslim to lower their gaze, not be easly influenced by the opposite sex and avoid adultery. To that end every child who intends to enter Ad Durrah IT Junior High School will be interviewed and various test will be carried out as well as parents will be interviewed to ensure that parents play a role in educating and developing their children,, especially female students in the application of Islamic values, especially the attitude of iffah. So that the values instilled at school and at home are in harmony. From the begining, the school has informed the student’s guardian about the agreement to work together in educating child is not an easly matter that can be done by the one party. For the reason, it is necessary to cooperate between the school and parents. Furthermore teacher, especially PAI teacher, who play a very important role in this case as people teaching Islamic religious lessons, the become role model for their student as an implementation of teaching of Islam itself. In his efforts to guide the stdents, the PAI teacher of SMP IT Ad Durrah tries to get closer to his student so that the student feel comfortable and nor awkward of even afraid of him. Then after a good relationship is created with the students, the advice, direction, guidance given by the PAI teacher will be happily carried out by the students.